High-Fat Diet Changes Fungal Microbiomes and Interkingdom Relationships in the Murine Gut - Timothy Heisel (American Society for Microbiology, 2017)
ABSTRACT Dietary fat intake and shifts in gut bacterial community composition are associated with the development of obesity. To date, characterization of microbiota in lean versus obese subjects has been dominated by studies of gut bacteria. Fungi, recently shown to affect gut inflammation, have received little study for their role in obesity. We sought to determine the effects of high-fat diet on fungal and bacterial community structures in a mouse model using the internal transcribed spacer region 2 (ITS2) of fungal ribosomal DNA (rDNA) and the 16S rRNA genes of bacteria. Mice fed a high-fat diet had significantly different abundances of 19 bacterial and 6 fungal taxa than did mice fed standard chow, with high-fat diet causing similar magnitudes of change in overall fungal and bacterial microbiome structures. We observed strong and complex diet-specific coabundance relationships between intra- and interkingdom microbial pairs and dramatic reductions in the number of coabundance correlations in mice fed a high-fat diet compared to those fed standard chow. Furthermore, predicted microbiome functional modules related to metabolism were significantly less abundant in high-fat-diet-fed than in standard-chow-fed mice. These results suggest a role for fungi and interkingdom interactions in the association between gut microbiomes and obesity. IMPORTANCE Recent research shows that gut microbes are involved in the development of obesity, a growing health problem in developed countries that is linked to increased risk for cardiovascular disease. However, studies showing links between microbes and metabolism have been limited to the analysis of bacteria and have ignored the potential contribution of fungi in metabolic health. This study provides evidence that ingestion of a high-fat diet is associated with changes to the fungal (and bacterial) microbiome in a mouse model. In addition, we find that interkingdom structural and functional relationships exist between fungi and bacteria within the gut and that these are perturbed by high-fat diet.